Pengukuran Kesiapan Kota Cerdas Berdasarkan SNI ISO 37122:2019 - Firmansyah, Esa; Binti Abd. Rahman, Aedah; Subiyakto, A'ang (Infoman's : Jurnal Ilmu-ilmu Informatika dan Manajemen, 2023)
This research aims to measure Smart City readiness using the SNI ISO 37122:2019 standard. This research uses quantitative methods to collect data and analyze Smart City readiness. The data collected includes indicators set out in the SNI ISO 37122:2019 standard. The results of this research can be used as a guide for the government and stakeholders in developing and improving Smart Cities.